PREPARATION OF TALENT DEVELOPMENT PROGRAM IN THE HUMAN RESOURCES UNIT OF THE GENERAL BUREAU OF THE REGIONAL SECRETARIAT OF WEST JAVA PROVINCE - Santoso, Kharismawati Zalfa; Maasir, Lidia (Jurnal Manajemen, 2026)
Abstract: This study aims to design a talent development program within the Human Resource Unit of the General Bureau, Regional Secretariat of West Java Province. The background of this research lies in the gap between government policies and the actual implementation of talent management, as reflected in the suboptimal results of the 2024 talent pool assessment. The assessment showed that the majority of civil servants were positioned in boxes 4, 5, and 6 of the Nine Box Matrix, representing a combination of moderate performance and potential. The study focuses particularly on employees in Box 5, as this group holds significant opportunities for improvement in both performance and potential. A qualitative research method with a descriptive approach was employed. Data were collected through interviews with relevant informants and document analysis. The formulation of the Talent Development Program in this research is based on the framework of Pella and Inayati (2011), which consists of five key stages: defining talent criteria, selecting the talent group, developing talent programs, placing talents in key positions, and conducting evaluation. The findings reveal that talent development practices for civil servants within the Regional Secretariat of West Java Province remain general in nature and have not been tailored to employees’ specific needs. Furthermore, interviews with staff in the HR Unit indicated that current civil servant development efforts are still primarily focused on technical training rather than long-term potential development.Keywords: Talent Management, Talent Development, Mentoring